Significance of bone marrow fibrosis in acute myeloid leukemia for survival in the real-world - Zhang, Xia; Wang, Fang; Yu, Jifeng; Jiang, Zhongxing (Frontiers in Oncology, 2022)
Acute myeloid leukemia (AML) is a highly heterogeneous hematologic malignancy characterized by the proliferation of myeloid blasts. Bone marrow fibrosis (BMF), characterized by increased deposition of reticulin or collagen fibers, can occur in AML. International authoritative guidelines do not mention AML patients with BMF and the reported studies are inconsistent. Therefore, we retrospectively analyzed the clinical data of newly diagnosed AML patients in our hospital and compared the clinical characteristics, gene mutations and prognosis of AML patients with or without BMF. We found AML patients with BMF tended to be older, were more prone to hepatosplenomegaly, their level of β2-MG was higher and they often had karyotypes associated with a poor prognosis. The proportion of AML patients without BMF was high in the intermediate-risk group and low in the high-risk group. The mutation rates of ASXL1 and TET2 genes were higher and that of CEBPA was lower in the BMF group. Multivariate analysis showed BMF had independent prognostic significance. AML patients without BMF had higher CR/CRi rate, and the time of hematopoietic recovery in patients achieving CR/CRi was longer in BMF group. The degree of BMF, prognostic level and blasts in peripheral blood were independent risk factors for CR/CRi in newly diagnosed AML. AML patients in the BMF group, especially those with BMF ≥ 2, had a lower OS rate. In age＜60 years old group, the higher the degree of BMF was, the shorter the median survival time and the lower the OS rate. In age ≥ 60 years old group, the median survival time in the BMF-1 and the BMF-2/3 groups was shorter. For AML with low, intermediate and high risk, there was always a lower OS rate in patients with BMF. The median survival of AML patients decreased with an increasing degree of BMF in different risk stratifications. BMF had no effect on OS of AML patients with HSCT. In conclusion, AML patients with BMF have a poor prognosis, and BMF was an independent prognostic factor for OS. The assessment of BMF was of great significance for the treatment efficacy and prognosis of newly diagnosed AML.